Characterizing visual fields in RPGR related retinitis pigmentosa using octopus static-automated perimetry - Buckley, TMW; Josan, AS; Taylor, LJ; Jolly, JK; Cehajic-Kapetanovic, J; MacLaren, RE (Association for Research in Vision and Ophthalmology, 2022)
Purpose: Peripheral visual fields have not been as well defined by static automated perimetry as kinetic perimetry in RPGR-related retinitis pigmentosa. This study explores the pattern and sensitivities of peripheral visual fields, which may provide an important end point when assessing interventional clinical trials.